That's How We Roll: The NASA K2 Mission Science Products and Their Performance Metrics. (10th June 2016) - Cleve, Jeffrey E. Van; Howell, Steve B.; Smith, Jeffrey C.; Clarke, Bruce D.; Thompson, Susan E.; Bryson, Stephen T.; Lund, Mikkel N.; Handberg, Rasmus; Chaplin, William J.
Abstract: NASA's exoplanet Discovery mission Kepler was reconstituted as the K2 mission a year after the failure of the second of Kepler 's four reaction wheels in 2013 May. Fine control of the spacecraft pointing is now accomplished through the use of the two remaining well-functioning reaction wheels and balancing the pressure of sunlight on the solar panels, which constrains K2 observations to fields in the ecliptic for up to approximately 80 days each. This pseudo-stable mechanism gives typical roll motion in the focal plane of 1.0 pixels peak-to-peak over 6 hr at the edges of the field, two orders of magnitude greater than typical 6 hr pointing errors in the Kepler primary mission. Despite these roll errors, the joint performance of the flight system and its modified science data processing pipeline restores much of the photometric precision of the primary mission while viewing a wide variety of targets, thus turning adversity into diversity. We define K2 performance metrics for data compression and pixel budget available in each campaign; the photometric noise on exoplanet transit and stellar activity timescales; residual correlations in corrected long-cadence light curves; and the protection of test sinusoidal signals from overfitting in the systematic error removal process. We find that data compression and noise both increase linearly with radial distance from the center of the field of view, with the data compression proportional to star count as well. At the center, where roll motion is nearly negligible, the limiting 6 hr photometric precision for a quiet 12th magnitude star can be as low as 30 ppm, only 25% higher than that of Kepler . This noise performance is achieved without sacrificing signal fidelity; test sinusoids injected into the data are attenuated by less than 10% for signals with periods upto 15 days, so that a wide range of stellar rotation and variability signatures are preserved by the K2 pipeline. At timescales relevant to asteroseismology, light curves derived from K2 archive calibrated pixels have high-frequency noise amplitude within 40% of that achieved by Kepler . The improvements in K2 operations and science data analysis resulting from 1.5 years of experience with this new mission concept, and quantified by the metrics in this paper, will support continuation of K2 's already high level of scientific productivity in an extended K2 mission.